Congenital common bile duct cyst in a 9-year-old girl - Cabrera Roca, María T; Badanián de García Fontes, Rosa (Cirugía del Uruguay, 2021)
We present a case of congenital cyst of common bile duct that takes it in its entirety. We highlight the peculiarity of absence jaundice and cirrhosis in this case. Having presented himself with the mask of an acute picture of the right upper quadrant which raised the diagnosis of subhepatic appendicitis or acute cholecystitis. The debut of the painting with acute dilation gallbladder that came to empty that huge cyst that was not touched as such in the first operation but impressed as a general dilation of the track bile. This variant is the first time that we see it described. We highlight the indemnity of the liver as an element of good prognosis, to which touch reaching up to cirrhosis maybe the evolution of some patients is due. We choose the cyst duodenostomy later to study the favorable of the case and the ease non-distorting performance no items and after discarding the other known procedures that are not we consider appropriate in this case. We consider the reduction of the cyst in the last cholangiography, acceptable to 21 days after the derivative intervention. I know will study in the future with x-rays contrasted bile duct and functional studies liver